Sustained Hyperresponsiveness of Dendritic Cells Is Associated with Spontaneous Resolution of Acute Hepatitis C - Pelletier, Sandy (American Society for Microbiology, 2013)
Some studies have reported that dendritic cells (DCs) may be dysfunctional in a subset of patients with chronic hepatitis C virus (HCV) infection. However, the function of DCs during acute HCV infection and their role in determining infectious outcome remain elusive. Here, we examined the phenotype and function of myeloid DCs (mDCs) and plasmacytoid DCs (pDCs) during acute HCV infection. Three groups of injection drug users (IDUs) at high risk of HCV infection were studied: an uninfected group, a group with acute HCV infection with spontaneous resolution, and a group with acute infection with chronic evolution. We examined the frequency, maturation status, and cytokine production capacity of DCs in response to the Toll-like receptor 4 (TLR4) and TLR7/8 ligands lipopolysaccharide (LPS) and single-stranded RNA (ssRNA), respectively. Several observations could distinguish HCV-negative IDUs and acute HCV resolvers from patients with acute infection with chronic evolution. First, we observed a decrease in the frequency of mature CD86(+), programmed death-1 receptor ligand-positive (PDL1(+)), and PDL2(+) pDCs. This phenotype was associated with the increased sensitivity of pDCs from resolvers and HCV-negative IDUs versus the group with acute infection with chronic evolution to ssRNA stimulation in vitro. Second, LPS-stimulated mDCs from resolvers and HCV-negative IDUs produced higher levels of cytokines than mDCs from the group with acute infection with chronic evolution. Third, mDCs from all patients with acute HCV infection, irrespective of their outcomes, produced higher levels of cytokines during the early acute phase in response to ssRNA than mDCs from healthy controls. However, this hyperresponsiveness was sustained only in spontaneous resolvers. Altogether, our results suggest that the immature pDC phenotype and sustained pDC and mDC hyperresponsiveness are associated with spontaneous resolution of acute HCV infection.